2008
DOI: 10.1016/s1808-8694(15)31390-2
|View full text |Cite
|
Sign up to set email alerts
|

Sudden hearing loss caused by labyrinthine hemorrhage

Abstract: Sudden sensorineural hearing loss is relatively frequent. In most cases, the etiology is not discovered. One of the possible causes for sudden deafness is inner labyrinth bleeding, which was difficult to diagnose before the advent of magnetic resonance imaging. The purpose of this paper is to report a case of sudden hearing loss caused by a labyrinthine hemorrhage, and to present a review of the literature on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…Haemorrhages in the cochlea have been associated with cases of sudden sensorineural hearing loss in humans (Salomone et al 2008). In addition, massive inner ear haemorrhage has been identified in humans as a cause for sudden deafness in cases associated with leukaemia (Schuknecht et al 1965), Buerger's disease (Kirikae et al 1962) or metastatic malignancy of the inner ear (Hoshino et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Haemorrhages in the cochlea have been associated with cases of sudden sensorineural hearing loss in humans (Salomone et al 2008). In addition, massive inner ear haemorrhage has been identified in humans as a cause for sudden deafness in cases associated with leukaemia (Schuknecht et al 1965), Buerger's disease (Kirikae et al 1962) or metastatic malignancy of the inner ear (Hoshino et al 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Blood in the endolymph and perilymph changes the hydrostatic pressure, which alters cochlear function and nerve stimulation. 5 BPPV in this patient may have developed sporadically and unrelated to the case, but there is also a strong possibility that both events were related. After an attack of vestibular neuritis, about one patient in three will develop posterior canal BPPV, usually within three months.…”
Section: Discussionmentioning
confidence: 84%
“…9 Two cases were reported to show improved hearing: Shinaharo et al documented an average 30dB hearing gain after steroid therapy on a non-profound down-sloping threshold curve 6 and Salomone et al reported an average 20dB hearing gain after unspecified medical therapy. 5 This patient's recovery was restricted to higher frequencies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…9 The association between LH and LO has not been fully demonstrated, but it is theorized that LH incites a reparative response that cascades from fibrosis to sclerosis and ultimately ossification of the inner ear structures. 13 SNHL is a well-recognized complication of SCD, and many previous studies reported high prevalence of SNHL.…”
Section: Original Researchmentioning
confidence: 99%